PERAN SELF AWARENESS DALAM MEMEDIASI PENGARUH SUPERVISI AKADEMIK PENGAWAS DAN KEMAMPUAN MANAJERIAL KEPALA SEKOLAH TERHADAP KOMPETENSI GURU - Dody Andrawan (Jurnal Pendidikan Ilmu Sosial, 2016)
This research aims to determine the role of self-awareness to mediate the effect of academic supervision of school supervisor and managerial skills of principals on teacher competence. The research method is quantitative research with path analysis. Samples were taken by using proportional random sampling of 198 respondents from 452 people who became teacher population. Results of path analysis with AMOS found that the direct influence of the academic supervision of school supervisor significantly to the competence of teachers and self awareness respectively 0.154 and 0.174. Direct influence managerial capacity principals are not significant to the competence of teachers. Hypothesis influence significant managerial skills principals to teachers’ self awareness to the value of coefficient are 0.289. Similarly, the effect of self-awareness hypothesis significantly to the competency of teachers with coefficient is 0.591. Self awareness as an intervening variable proved able to mediate significant effect relationship between exogenous variable to endogenous variable shown by the results of Sobel test.